Forces generated by Macintosh and GlideScope® laryngoscopes in four airway‐training manikins1. (10th April 2013) - Lee, C.; Russell, T.; Firat, M.; Cooper, R. M.
Summary We measured forces generated by Macintosh and GlideScope® laryngoscope blades during airway intubation by 16 participants in four manikins: Laerdal® SimMan; TruCorp AirSim™ Advance; Laerdal® Airway Management Trainer; and Ambu® Airway Man. Both laryngoscopes generated the least force in the Laerdal Airway Management Trainer and the most in the Ambu Airway Man. The respective median (IQR [range]) forces generated by the Macintosh blade were 2 (1–4 [1–7]) N vs 9 (7–13 [5–16]) N, p = 0.00004, with peak forces 9 (5–11 [3–16]) N vs 18 (12–22 [3–31]) N, p = 0.0004. The respective average and peak forces generated by the GlideScope blade were 1 (1–2 [0–3]) N vs 4 (3–5 [2–6]) N, p = 0.00001, and 4 (2–7 [0–12]) N vs 7 (4–9 [3–18]) N, p = 0.054.